A case of descending mediastinitis caused by Streptococcus pyogenes harboring genotype emm25 and sequence type 660. Issue 6 (June 2017) - Ohya, Hiroaki; Mori, Nobuaki; Hayashi, Tetsuro; Minami, Shujiro; Higuchi, Akiko; Takahashi, Takashi
Abstract: Descending mediastinitis caused by Streptococcus pyogenes (group A streptococcus, GAS) is rare among cases of invasive GAS infection. In this report, we describe a case of a cervical abscess and secondary descending mediastinitis in a previously healthy 39-year-old Japanese man. The patient presented with a 2-week history of a sore throat, and subsequently developed an abscess and descending mediastinitis. We treated the cervical abscess using ampicillin/sulbactam and drainage, and GAS was subsequently isolated in two blood cultures from the patient's admission. Microbiological analyses revealed that the isolate harbored genotype emm25 and sequence type (ST) 660. This strain was susceptible to erythromycin (minimum inhibitory concentration [MIC]: ≤0.12 μg/mL), resistant to minocycline (MIC: >4 μg/mL), and possessed the tet (M) determinant. Although we have reviewed the literature regarding the clinical and microbiological characteristics of descending mediastinitis cause by GAS, little is known regarding epidemiological and clinical characteristics of emm25 /ST660 GAS. Furthermore, to best of our knowledge, this is the first reported case of descending mediastinitis caused by emm25 /ST660 GAS. Therefore, physicians should be aware of case with a cervical abscess and secondary descending mediastinitis caused by GAS infection, even if the patient is immunocompetent.